Front and pipe spikes in female elite volleyball players: implications for the improvement of pipe spike techniques - Masumura, M.; Quispe, M.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The pipe spike was recently incorporated in offensive combinations increasing the complexity of volleyball tactics and making games more sophisticated. Such combinations are now seen in female games as a strategy of feinting to overcome the block more effectively. Although some investigations analysed front spike techniques, no study has been done on the pipe spike motion for female elite players in official games. Therefore, the purpose of this study was to compare the kinematics of front and pipe spikes of female elite volleyball players, and obtain insights into the techniques for pipe spike motion.